2010
DOI: 10.1016/j.jcin.2010.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Percutaneous Coronary Intervention in Intermediate Coronary Artery Disease

Abstract: Both FFR- and IVUS-guided PCI strategy for intermediate coronary artery disease were associated with favorable outcomes. The FFR-guided PCI reduces the need for revascularization of many of these lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
1
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(61 citation statements)
references
References 23 publications
2
52
1
4
Order By: Relevance
“…This is within the range reported in previous studies assessing specifically intermediate-grade CAS on CCA [27,28] and on CCTA [13]. However, our reported prevalence was substantially higher than the rate of 18 % (10/56) reported by Kristensen et al [26] but lower than the rate of 45 % reported by Rossi et al [12].…”
Section: Discussionsupporting
confidence: 77%
“…This is within the range reported in previous studies assessing specifically intermediate-grade CAS on CCA [27,28] and on CCTA [13]. However, our reported prevalence was substantially higher than the rate of 18 % (10/56) reported by Kristensen et al [26] but lower than the rate of 45 % reported by Rossi et al [12].…”
Section: Discussionsupporting
confidence: 77%
“…The FAME study reported favorable outcomes of FFR-guided PCI when compared with conventional angiography guided PCI [11,22]. FFR also reduces the need for revascularization of many of intermediate lesions [31], and is associated with improved health and economic outcomes compared to treatment based on angiography alone [6,32]. As a result, FFR guidance during PCI has received a class 1A recommendation from the European Society of Cardiology [33], and a class IIA recommendation from the American College of Cardiology [34]; however, FFR is still underutilized clinically with <10% of PCI performed in the absence of clinical evidence of ischemia [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…The FFR was measured after intracoronary administration of adenosine (40 g in the right and 80 to 120 g in the left coronary artery) to induce maximum hyperemia, as previously described. 11,12 The lowest FFR value was selected after Ն2 measurements.…”
Section: Methodsmentioning
confidence: 99%